Analysis of retinal microstructure and electrophysiology in eyes following pars plana vitrectomy and membrane peeling for vitreomacular interface disorders - I-Hsien Chen; Meng-Syuan Li; Chia-Li Tseng; Hung-Pin Tu; Shwu-Jiuan Sheu (BMC Ophthalmology)
Abstract Purpose To investigate the relationship between retinal structural biomarkers using spectral-domain optical coherence tomography (SD-OCT) and macular function before and after surgery. Methods Forty-four eyes of 44 patients were included. Ophthalmological examinations included visual acuity (VA), intraocular pressure, OCT angiography (OCTA), and multi-focal electroretinography (mf-ERG) at baseline (pre-surgery) and post-operative follow-up. The ILM texture during peeling was graded by the surgeon as follows: Grade 1, fragile; Grade 2, easy to peel in a sheet; and Grade 3, sticky. The cross-sectional area of the ganglion cell layer and central retinal thickness in the fovea were evaluated using ImageJ software of SD-OCT. The presence of a dissociated optic nerve fiber layer (DONFL) was evaluated using en face OCTA images. mf-ERG results are shown as the ratio between the average amplitudes from rings 1 and 2 (central) and rings 4 and 5 (peripheral): the P1 ratio. Results Based on the SD-OCT morphological characteristics of the foveal area, 14 cases were classified into ERM group 1 (mainly outer retinal thickening or more tenting of the outer retina), 11 into ERM group 2 (prominent inner retinal thickening), 9 into ERM group 3 (ERM with macular hole), and 10 into ERM group 4 (full thickness macular hole without ERM and vitreomacular traction without ERM). Morphological characteristics were correlated with ILM texture (p = 0.0031) and DONFL (p < 0.0001). Group 2 and group 3 ERM had a stickier ILM when peeling and showed DONFL in 100% of the cases. Group 1 ERM had a more fragile ILM when peeling and did not result in DONFL. ILM texture was also correlated with DONFL (p < 0.0001), in which sticky ILM resulted in DONFL after the operation. Eyes with DONFL showed a greater decrease in ganglion cell complex/central retinal thickness in the foveal area, slow P1 ratio recovery, and slower VA improvement. Conclusions ERM with prominent inner retinal structural changes are likely to have a stickier ILM when peeled, leading to a subsequently DONFL. The appearance of DONFL results in an initial decrease in macular function recovery and slower post-operative visual improvement. Surgeons should be more delicate when peeling sticky ILM, especially in eyes with ERM with prominent inner retinal thickening or macular holes.